SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KELAYAKAN PENGAJUAN SERTIFIKASI GURU DENGAN METODE SIMPLE ADDITIVE WEIGHTING (STUDI KASUS : MA AL MUHAJIRIN JANTI JOGOROTO JOMBANG) - Budiman Budiman; Umam Baharudin; Winarti Winarti (STMIK Dian Cipta Cendikia Kotabumi, 2021)
Formal educational institutions have an important task to prepare quality Indonesian human resources (HR) in the future. In this school education environment, professional teachers hold the main key for improving the quality of future human resources (HR) and teachers are professionals who carry out the main tasks and functions of improving the knowledge, skills, and attitudes of students as Indonesian human assets for the future. In the process of quality education, it is an obligation and obligation that is required for every school, to have certified teachers so that education can increase and can affect student achievement. Decision-making system as a set of model-based procedures for data processing and assessment. to assist schools in determining teachers who are eligible to receive certification with criteria namely pedagogic, personality, social, professional. The purpose of this research is to help decision makers in the selection process easily and quickly. The simple additive weighing (SAW) method to provide decisions on the selection process for submitting teacher certification. The system developer method uses the waterfall method. An educator certificate is a requirement for proof that teachers meet educational professional standards.